Tabanni Concept of Al-Quran Perspective: In The Study of Ijtimai Interpretation - Zulfia Malyan*; Jaka Ghianovan; Abil Ash (Riwayat: Educational Journal of History and Humanities, 2024)
This article aims to elucidate the issues that arise when individuals undertake the process of child adoption, with reference to the principles delineated in the Qur'an. The practice of treating a non-biological child as one's own is often deemed acceptable, this is evident from the prevalence of adoptive parents who assert their adopted children as their biological offspring. This study employs library research utilizing a thematic exegesis method. The analysis integrates interpretations from the "Al-Munir" exegesis by Wahbah Az-Zuhaili, the Ayat Suci Lenyepaneun exegesis by M. Emon Hasim, and the "Al-Mishbah" exegesis by M. Quraish Shihab on Surah Al-Ahzab verses 4-5. The findings indicate that "Tabanni," which means "considering someone else's child as one's own," clearly does not proscribe the act of adopting a child but rather prohibits the act of claiming an adopted child as a biological one. This injunction also seeks to abolish the pre-Islamic Arabian practice during the Jahiliyah era, wherein adopted children were considered biological. Muslims who adopt children are mandated to care for and love their adopted children as their own, with the stipulation that an adoptive father does not serve as the marriage guardian for his adopted daughter and that adoptive parents and adopted children do not have mutual inheritance rights.